Social anxiety from the Corona pandemic (COVID 19) : Theoretical Psychological Study - Abass, Zalzalah Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
Specialists in social and psychological sciences have paid attention to calamities, crises, social events and the spread of epidemics that develop rapidly and leave their mark on the social system. Some societies have faced severe and difficult dangers and exciting suffering that led to disruption in the unity of the community and its internal construction. Such cases put social construction in unfamiliar situations as a result of extreme suffering .So, this construction has become unable to meet the needs of individuals, when the construction becomes weak in its performance of the responses required to meet the desires of its members and satisfy them as a result of the state of rupture and weak interconnectedness in the nature of the achievement of its forms creates phenomena that may be difficult to predict or knowledge of the effects and problems that will be left to them, and perhaps the most important What situations such emergency and temporary structures produce are social anxiety.The emergency that the world is witnessing today requires researchers to provide different scientific insights about the Corona epidemic that threatens human life on the surface of the planet, so we will try in this theoretical study to shed light on some of the effects of this virus on human life.